The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s0006-87051999000200015
|View full text |Cite
|
Sign up to set email alerts
|

Resposta de cultivares de arroz-de-sequeiro à calagem

Abstract: RESUMODesenvolveu-se um experimento de campo, em Assis (SP), em areia quartzosa com capacidade de troca de cátions igual a 35 mmol c .dm -3 e 9% de saturação por bases. Estudou-se a resposta dos cultivares de arroz-de-sequeiro (Oryza sativa L.) IAC 25, IAC 47, IAC 165 e Araguaia às doses 0, 2, 4 e 6 t.ha -1 de calcário dolomítico e 2 t.ha -1 de calcítico. O calcário foi aplicado em outubro de 1991 e as avaliações, realizadas no ano agrícola 1992/93. Aos 20 dias da emergência das plantas, amostrou-se a parte aé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
(6 reference statements)
1
3
0
2
Order By: Relevance
“…2a and 2b), as dolomitic limestone is an excellent source of these nutrients. Similar results were obtained by Duarte et al (1999) studying the response of rice cultivars to liming. The other macronutrients were not influenced by liming, and their contents were in the adequate range in all of the treatments (Cantarella et al, 1996), except for K, which contents were below this range.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…2a and 2b), as dolomitic limestone is an excellent source of these nutrients. Similar results were obtained by Duarte et al (1999) studying the response of rice cultivars to liming. The other macronutrients were not influenced by liming, and their contents were in the adequate range in all of the treatments (Cantarella et al, 1996), except for K, which contents were below this range.…”
Section: Resultssupporting
confidence: 84%
“…Results indicate that liming had no effect on the availability of these nutrients in the soil (Table 3). Duarte et al (1999) also reported no effect of liming on the contents of Cu and Zn in upland rice cultivars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em todos os tratamentos as concentrações estavam dentro da faixa considerada adequada , com exceção do Fe, cujos valores ficaram abaixo dessa faixa. De acordo com Fageria (1982), Ferreira et al (1986) e duarTe et al (1999, existem diferenças entre as cultivares de arroz quanto às suas respostas ao alumínio no solo e à calagem, apesar do arroz ser uma espécie adaptada às condições de acidez do solo (Fageria, 2000;duarTe et al, 1999).…”
Section: Resultsunclassified
“…O arroz de terras altas pode ser uma opção interessante, por ser considerado adaptado a essas condições (Fageria, 2000), entretanto dentro da espécie existem cultivares que diferem em sua resposta ao estresse de Al e à calagem (Fageria, 1982;Ferreira et al, 1986;duarTe et al, 1999). Na cultura do feijão, também foram observadas respostas diferenciadas de cultivares à calagem (vale, 1994; silva, 2002), podendo, as mais tolerantes à acidez, serem utilizadas no período em que o calcário aplicado superficialmente ainda não promoveu correção da acidez, principalmente, nas camadas sub-superficiais do solo.…”
Section: Introductionunclassified